ChemInform Abstract: Tetraalkylammonium Salts as Hydrogen‐Bonding Catalysts. Issue 17 (April 2016) - Shirakawa, Seiji; Liu, Shiyao; Kaneko, Shiho; Kumatabara, Yusuke; Fukuda, Airi; Omagari, Yumi; Maruoka, Keiji
Abstract: Newly designed tetraalkylammonium salts (TAS) are investigated as hydrogen‐bonding catalysts for coupling reactions of chlorodihydroisoquinolines (I) with ketene acetals (II) or silyl enol ethers (IV).